Influence of supporting amorphous carbon film thickness on measured strain variation within a nanoparticle. Issue 43 (31st October 2017) - Settem, Manoj; Rajak, Piu; Islam, Mahabul; Bhattacharyya, Somnath
Abstract : Supporting amorphous carbon film thickness introduces an artefact in measured strain variation within a nanoparticle using HRTEM images. Abstract : Strain variation within a nanoparticle plays a crucial role in tuning its properties. High Resolution Transmission Electron Microscopy (HRTEM) images of a nanoparticle supported on amorphous carbon film are used to determine the strain variation. Experimental measurements in this present study on a single crystalline silver nanoparticle exhibited an unexpected high strain variation. Generally, the influence of carbon film is not accounted for during interpretation of measured strain variation. However, experimental observations raise the question whether the supporting carbon film alters the measured strain variation. In order to address this, strain variation within a simulated Ag nanoparticle supported on an amorphous carbon is measured with varying film thicknesses. The results show that supporting carbon film thickness introduces an artefact leading to more strain variation than what is present within an unsupported nanoparticle. Moreover, the variation increases with increasing supporting carbon film thickness. This effect is more pronounced in a thinner nanoparticle. Without considering this influence, the interpretation of strain within a nanoparticle may introduce severe errors which in turn will affect the tunability of desirable properties for different applications. Since strain measurement depends on the accuracy of the atomic position, the interpretation of any result using the atomic position from HRTEM images of a nanoparticle should consider the influence of supporting film.